Effect of Power Distance and Uncertainty Avoidance on Employees' Job Performance: Preliminary Findings - Chien Jie, Ivy Lau; Munshid Harun, Mohd Zainal; Djubair, Rahmat Aidil (Journal of Technology Management and Business, 2020)
This study examines the relationship between corporate culture and employees' job performance in a multinational company operated in Malaysia. Malaysia is well-known as a culturally-diverse country in the world. Therefore, the selected multinational company needs to assess its internal cultures as workers from different ethnical backgrounds work together. The general objective of this study is to determine corporate culture's effect on job performance among the workers in the targeted multinational company. The selected cultural dimensions to study corporate culture were power distance and uncertainty avoidance, from a theory developed by Geert Hofstede. The research design adopted for the current study was a quantitative correlation design. A self-administered questionnaire was developed and distributed to the targeted respondents for obtaining primary data. IBM SPSS 25.0 was employed to analyse reliability analysis, frequency analysis, correlation analysis, and regression analysis. This study identified that both power distance and uncertainty avoidance exert a significant and moderately positive effect on employees' job performance. Hence, the selected multinational company should be alert and keep an eye on enhancing and strengthening the two said dimensions since it gives impact on the workers' job performance.